Pragmatics Implicature Analysis of Police Interrogation: Forensic Linguistics Analysis - Santoso, Dwi; Apriyanto, Sigit (International Journal of Psychosocial Rehabilitation, 2020)
–Language is a means for speakers to express their opinions and ideas. In the legal context, communication made between investigators and witnesses or suspects is created in such a way that the message is conveyed properly. Elements of communication are needed, especially by witnesses or suspects who are being interrogated by the police. Interrogators will be able to convey their hearts and minds precisely when interrogators use humane methods, including conversational implicature. The purpose of this study is to conduct forensic interrogation to identify the implications of language conversation from the perspective of the symbolic meaning of legal language. The research population is the language used by the interrogators and those involved in the interrogation. The sample is a conversation during an interrogation in a case of fraud and traffic. Data collection is done by using transcription data obtained which is then analyzed. The principle of discourse analysis is used to analyze data based on conversational implicature. The formal method is used to describe the forms and patterns of interrogation languages, while the informal method is used to classify data based on the implications of the speaker’s conversation. The results of this study indicate that the use of conversational implicature in the police interrogation process can create humanist communication without having to use violent techniques. Investigators need to know more about the implicature of the conversation.